Static and dynamic studies of hydrogen adsorption on nanoporous carbon gels - Czakkel, Orsolya; Nagy, Balázs; Dobos, Gábor; Fouquet, Peter; Bahn, Emanuel; László, Krisztina (International journal of hydrogen energy, 2019)
Although hydrogen is considered to be one of the most promising green fuels, its efficient and safe storage and use still raise several technological challenges. Physisorption in porous materials may offer an attractive means of H2 storage, but the state-of-the-art capacity of these kinds of systems is still limited. To overcome the present drawbacks a deeper understanding of the adsorption and surface diffusion mechanism is required along with new types of adsorbents developed and/or optimised for this purpose. In the present study we compare the hydrogen adsorption behaviour of three carbon gels exhibiting different porosity and/or surface chemistry. In addition to standard adsorption characterisation techniques, neutron spin-echo spectroscopy (NSE) has been also applied to explore the surface mobility of the adsorbed hydrogen. Our results reveal that both the porosity and surface chemistry of the adsorbent play a significant role in the adsorption of H2 in these systems.
Gesehen am 19.11.2019